Time- and dose-dependent seeding tendency of exogenous tau R2 and R3 aggregates in cells - Annadurai, Narendran; Hrubý, Jiří; Kubíčková, Agáta; Malina, Lukáš; Hajdúch, Marián; Das, Viswanath (Biochemical and biophysical research communications, 2023)
Tauopathies are a group of neurodegenerative diseases categorised into three types, 3R, 4R, or 3R+4R (mixed) tauopathies, based on the tau isoforms that make up the aberrant filaments. It is supposed that all six tau isoforms share functional characteristics. However, differences in the neuropathological features associated with different tauopathies offer the possibility that disease progression and tau accumulation may vary depending on the isoform composition. The presence or absence of repeat 2 (R2) in the microtubule-binding domain defines the type of isoform, which might influence tau pathology associated with a particular tau isoform. Therefore, our study aimed to identify the differences in the seeding propensities of R2 and repeat 3 (R3) aggregates using HEK293T biosensor cells. We show that the seeding induced by R2 was generally higher than by R3 aggregates, and lower concentrations of R2 aggregates are sufficient to induce seeding. Next, we found that both R2 and R3 aggregates dose-dependently increased triton-insoluble Ser262 phosphorylation of native tau, which is only visible in cells seeded with higher concentrations (12.5 nM or 100 nM) of R2 and R3 aggregates, despite the seeding by the lower concentrations of R2 aggregates after 72 h. However, the accumulation of triton-insoluble pSer262 tau was visible earlier in cells induced with R2 than in R3 aggregates. Our findings suggest that the R2 region may contribute to the early and enhanced induction of tau aggregation and define the difference in disease progression and neuropathology of 4R tauopathies.
Keywords: Tau seeding; Biosensor cells; tau Proteins; Humans; Protein Binding; HEK293 buňky; vazba proteinů; Alzheimerova nemoc; proteiny tau; HEK293 Cells; Protein Isoforms; protein - isoformy; Tauopathies; lidé; tauopatie; Tau protein; Alzheimer Disease; Alzheimer's disease